Public Perceptions toward TikTok : A Critical Analysis - Chapagai, Shiva Dutta; Adhikari, Bhabani; Karki, Dan Singh (Community College Research Journal, 2025)
This study looks at how people feel about TikTok, especially how they use it, how it affects their mental health, and how it affects their professional growth. TikTok is a popular social media site that is mostly known for its entertainment value. It has become a global phenomenon, especially among young people. A quantitative methodology employing a descriptive research design was utilized, gathering data from 300 participants aged 18 and above. The results show that the main reason people used TikTok was for entertainment, with 81.5% of users saying it was fun. Other reasons, like making friends, being creative, and learning, were seen as less important. Even though many people liked TikTok, 78% of those who answered said they didn’t think it helped them learn work-related skills. Also, 32% of users said that the platform could lead to addictive behaviors, even though it didn’t have a completely bad effect on mental health. The study emphasizes TikTok’s primary function as a source of entertainment, while also expressing apprehensions regarding its impact on productivity and mental health. Subsequent investigations ought to examine the enhanced application of TikTok in educational, corporate, and mental health domains.